Ageritin from poplar mushrooms: scale-up purification and cytotoxicity towards undifferentiated and differentiated SH-SY5Y cells. Issue 10 (23rd August 2019) - Ragucci, Sara; Pacifico, Severina; Ruocco, Maria Rosaria; Crescente, Giuseppina; Nasso, Rosarita; Simonetti, Martina; Masullo, Mariorosario; Piccolella, Simona; Pedone, Paolo V.; Landi, Nicola; Di Maro, Antimo
Abstract : Ageritin from poplar mushroom is a valuable selective neurotoxin towards undifferentiated neuroblastoma SH-SY5Y cells. Abstract : Ageritin is the first reported ribotoxin-like protein from basidiomycetes fungi. It can induce ribosomal integrity damage and translation block, and interferes with mitochondrial redox activity of some glioma and neuroblastoma cell lines. Herein, Ageritin has been investigated as a valuable neurotoxin towards either undifferentiated or retinoic acid (RA)-differentiated SH-SY5Y neuroblastoma cells showing a selective cell toxicity against undifferentiated cells. MTT and sulforhodamine B (SRB) assays highlighted that Ageritin markedly decreases the mitochondrial redox activity and viability of undifferentiated cells, meanwhile inducing evident morphological changes eliciting neuronal-like appearance in these cells. Data from lactate dehydrogenase release assay, cytofluorimetric analysis and caspase-3 enzymatic activity measurement suggest that Ageritin promotes cell death through a caspase-dependent apoptotic pathway. The Z-VAD-FMK caspase inhibitor was able to prevent this apoptotic pathway activation. Based on the interesting behaviour of Ageritin vs . SH-SY5Y cells, the development of a scale-up procedure to obtain the purified protein in larger amounts (yield 2.5 mg per 100 g) has been optimized.